KAJIAN HERMENEUTIK FRASA “MEMBENCI ESAU” BERDASARKAN MALEAKHI 1:2-3 DAN IMPLIKASINYA BAGI ORANG KRISTEN MASA KINI - Niel Tangibali; Markus Lingga (Misioner, 2021)
Hermeneutic Study of the Phrase “Hate Esau” Based on Malachi 1:2-3 and Its Implications for Christians Today. This research is focused on hermeneutical studies to find the meaning of the phrase “Hate Esau” based on Malachi 1:2-3 and its implications for Christians today. This study uses a qualitative research with exegesis hermeneutic method in which the researcher exegises the phrase “Hate Esau” based on Malachi 1:2-3. Based on the results of the exposition of the book of Malachi 1:2-3, the researchers found the meaning of the phrase "Hate Esau" as well as its theological impact and its practical impact on Christians today.